2018
DOI: 10.1039/c7tc04823h
|View full text |Cite
|
Sign up to set email alerts
|

Organic field-effect transistors processed by an environmentally friendly non-halogenated solvent blend

Abstract: Based on Hansen solubility parameter analysis, this study employed a non-halogenated binary solvent blend of mesitylene and acetophenone to closely mimic the efficiency of dichlorobenzene, for widely used conjugated polymers used for OFETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Noh et al reported the fabrication of P184-based OFET's, processed using a non-halogenated binary solvent system, by using the HSP analysis method. 88 The P184-based OFET exhibited a high mobility of 0.574 cm 2 V À1 s À1 , which could be attributed to the properties of the pre-aggregated phase of the binary solvent blend consisting of mesitylene and acetonitrile.…”
Section: F I G U R E 2 4 Chemical Structures Of Ndi-and Pdi-based Polymers (P181-p202) Ndi Naphthalenediimide; Pdi Perylenediimidementioning
confidence: 96%
“…Noh et al reported the fabrication of P184-based OFET's, processed using a non-halogenated binary solvent system, by using the HSP analysis method. 88 The P184-based OFET exhibited a high mobility of 0.574 cm 2 V À1 s À1 , which could be attributed to the properties of the pre-aggregated phase of the binary solvent blend consisting of mesitylene and acetonitrile.…”
Section: F I G U R E 2 4 Chemical Structures Of Ndi-and Pdi-based Polymers (P181-p202) Ndi Naphthalenediimide; Pdi Perylenediimidementioning
confidence: 96%
“…Crude product was recrystallized in CHCl 3 -hot ethanol to obtain 1.67 g product, with 84% yield. 1 4 (8 mg, 0.05 eq.) were added to a 50 mL round-bottom flask.…”
Section: Synthesis Of Tris(4-bromophenyl)aminementioning
confidence: 99%
“…Solution processable π-conjugated semiconductors, a subset of organic materials, has progressively attracted much attention from both academic and industrial applications as the best candidate for lightweight, transparent, flexible electronic devices with less production cost for high throughput processing [1][2][3][4]. These materials have been fabricated as active organic layers in organic field-effect transistors (OFETs), organic photovoltaic (OPV) cells, and organic light emitting diodes (OLEDs) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this work, Noh et al exploited other non-chlorinated solvents, such as acetophenone and mesitylene, to generate OFETs with comparable field-effect mobilities to that of dichlorobenzene. 29 Many other important works on the fabrication of organic electronics using green materials and processing, as well as new tool to identify and develop new green solvent systems for printed electronics have been summarized and reported in recent literature. 27,[30][31][32][33] Dendronized polymers are an interesting platform for the preparation of advanced semiconductors, particularly in biological applications and for the formation of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%